2017
DOI: 10.1111/petr.12984
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic risks vary by weight status in pediatric kidney and liver transplant recipients: A cross‐sectional, single‐center study in the USA

Abstract: There is an increasing need to understand long-term metabolic changes and resultant comorbidities because life expectancy is increasing after pediatric kidney and liver transplants. We evaluated differences in classic and novel cardiometabolic biomarkers among obese and normal weight adolescent transplant recipients. We enrolled a total of 80 adolescent (mean±SD, 14.8 years ±3.0) transplant recipients (63 kidney, 17 liver) with mean duration from transplantation of 6.0 (±4.1) years. Among kidney transplant rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Obese transplant recipients who were obese by WHr were also noted to have elevated leptin levels compared with lean transplant recipients. This finding is in agreement with that of He et al, who demonstrated higher leptin levels in pediatric kidney transplant recipients with obesity. Elevated leptin is a biomarker for increased CV risk due to the hormone's proatherogenic effects that are associated with hypertension, oxidative stress, endothelial dysfunction, and subsequent vascular dysfunction …”
Section: Discussionsupporting
confidence: 93%
“…Obese transplant recipients who were obese by WHr were also noted to have elevated leptin levels compared with lean transplant recipients. This finding is in agreement with that of He et al, who demonstrated higher leptin levels in pediatric kidney transplant recipients with obesity. Elevated leptin is a biomarker for increased CV risk due to the hormone's proatherogenic effects that are associated with hypertension, oxidative stress, endothelial dysfunction, and subsequent vascular dysfunction …”
Section: Discussionsupporting
confidence: 93%
“…Although the association between lower motor proficiency in children who are overweight or obese is established in the general population, 39,40 it is of particular concern in children post-LT, as they are at a higher risk for clustering of metabolic risk factors. 5 In healthy children, motor proficiency has been associated with higher levels of PA, 11,41 a key intervention for lowering the risk of cardiometabolic disease. 6 Our results highlight the need to address motor proficiency post-LT, including strength, speed, agility, and balance activities, to help reduce the risk of cardiometabolic morbidity in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, higher weight z ‐scores were associated with lower scores on strength, balance and running speed and agility measures. Although the association between lower motor proficiency in children who are overweight or obese is established in the general population, 39,40 it is of particular concern in children post‐LT, as they are at a higher risk for clustering of metabolic risk factors 5 . In healthy children, motor proficiency has been associated with higher levels of PA, 11,41 a key intervention for lowering the risk of cardiometabolic disease 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations